Upper Perené Arawak narratives of history, landscape, and ritual - Mihas, Elena; Santos Pérez, Gregorio; Rosas Rodríguez, Delia (University of Nebraska Press, 2014)
"A comprehensive bilingual collection of Ashéninka Perené Arawakan oral literature, including traditional narratives, ethnographic accounts of old customs and rituals, contemporary women's autobiographical stories, songs, chants, and ritual speeches"--